Environmental attitudes of polluting SMEs: Qualitative insights from a low‐income developing country. Issue 4 (20th July 2020) - Hasan, Md Nazmul; Anastasiadis, Stephanos; Spence, Laura J.; Uba, Chijioke D.
Abstract: In this paper we explore the environmental attitudes of polluting SMEs (small‐scale firms that produce or deal with environmentally sensitive goods) from the perspective of owner/managers in a low‐income developing country context. Utilising extensive qualitative data from SMEs operating in two of the most polluting industries in Bangladesh—leather tanning and textile dyeing, we provide a qualitative understanding of how the owner/managers formulate, interpret, and judge the environmental issues related to their business operations. Our analysis indicates that the owner/managers hold four types of distinct environmental attitudes towards the environmental issues relevant to their businesses: conscious, instrumental, resentful, and complacent. We differentiate these attitudes based on three salient dimensions: owner/managers' general interest in environmental issues, their commitment to act in environmentally responsible ways, and key stakeholder focus. Our study contributes to the small business literature by identifying complexity in the owner/managers' responses to relevant environmental issues and offering a nuanced understanding of the environmental attitudes of polluting SMEs in a low‐income developing country context. In addition, our findings inform policies designed with the practical needs of small‐scale polluting firms in mind.